Beyond the feminization thesis : gender and Christianity in modern Europe - Pasture, Patrick, 1961- (KADOC studies on religion, culture, and society, 2012)
Since the 1970s the feminization thesis has become a powerful trope in the rewriting of the social history of Christendom. However, this 'thesis'' has triggered some vehement debates, given that men have continued to dominate the churches, and the churches themselves have reacted to the association of religion and femininity, often formulated by their critics, by explicitly focusing their appeal to men. In this book the authors critically reflect upon the use of concepts like feminization and masculinization in relation to Christianity. By presenting case studies that adopt different gendered.